Atenção à saúde materno-infantil no Programa Saúde da Família (PSF): limites e possibilidades para a prevenção de deficiências na infância - Souza, Carina Pimentel (2010)
It is known that most cases of deficiency in childhood can be avoided or attenuated and, although the causes are related to several factors, most of the times, they are due to lack of access, quality or organization of health practices and services . This study about deficiency prevention on childhood from attention to maternal - infant health, in the Family Health Program, by Family Health Teams (FHT) of Sanitary District Cabula - Beiru, in Salvador, Bahia, has the purpose of analyze the actions developed by Family Health teams in prenatal and infant Growing and Development Accompaniment (GDA) to prevent childhood deficiencies and point their limits and possibilities. It is a qualitative research that uses as techniques of data collection interviews with semistructured guide and systematic observation. The subjects of the study were the fifteen professionals that form the FHTs (doctors, nurses, nurse technicians and auxiliary and communitary health agents) and sixteen users (genitors in prenatal services and mothers from the GDA children). The technique of content analysis from Bardin was used to the analysis of data. The study signals that although the teams follow the same principles and orientations to the services and practices organization, they distinguish from each other in the manner they organize practices and in the activities developed in attention to maternal - infant health, this manner multiprofissional work, collaborative, with demand anticipation and articulated interventions in health promotion, prevention, assistance and recovery actions from people needs. The limits to deficiency prevention pointed out are the need of organization of services network, coresponsibility, the need of permanent education, the lack of unity of FHT and the socioeconomic context of families. The possibilities pointed out are the foot, eye and ear tests, the actions of health education, the community health agents link and work. The study finishes reaffirming the existence of possibility of prevention of childhood deficiencies and pointing that integrality constitutes the major challenge in order to make effective childhood deficiencies prevention, traversing practices, work and public health politics organization, from intersectoral actions.